(untitled) (Cadernos de Sociomuseologia, 2023)
In the search for practices that link education (in a Freirean sense) with a critical reflection upon the past aimed at empowering citizens in shaping their future deliberately, this paper aims to explore the common ground between the fields of museology and urban planning reflecting upon trans-national and undisciplined intersections. After recalling the debate about trans-disciplinarity and undiscipline as an evolutionary tendency of academic (and non-academic) discourses emerging in various contexts and fields of knowledge, authors explore the concept and practices of insurgencies. The paper presents such emerging trends aimed at making some forms of museology more open to communities and, simultaneously, some forms of community-based planning processes anchored to a rediscovery of the past as a means for reimaging the future. Authors argue that bridging insurgent forms of urban planning and museologies may contribute to opening new forms and trajectories of emancipation, grounded on a multifaceted awareness of the past and an ethos of socio-ecological justice for the now. Keywords: ecomuseums; community museums; community-based planning; landscape; territorial heritage; nouvelle muséologie